Molecular dynamics of dibenz[a, h]anthracene and its metabolite interacting with lung surfactant phospholipid bilayers1. Issue 32 (28th August 2015) - Padilla-Chavarría, Helmut I.; Guizado, Teobaldo R. C.; Pimentel, Andre S.
<x xml:space="preserve">Abstract</x> Dibenz[a, h]anthracene and its metabolite may form aggregates, which have implications in the clearance process of the lung surfactant phospholipid bilayers.